PENGGUNAAN IMPLIKATUR DAN PRESUPOSISI DALAM FILM MENCURI RADEN SALEH KARYA ANGGA DWIMAS SASONGKO - Aprillah Syafira; Anshari Anshari; Muhammad Alfian Tuflih (Fakultas Bahasa dan Sastra Indoensia, 2024)
This research aims to describe the use of implicatures and presuppositions found in the films analyzed. This type of research is qualitative. The data in this research is in the form of dialogue spoken by the actors. The data source for this research is the script and film Mencuri Raden Saleh by Angga Dwimas Sasongko. The results of this research show that the use of implicatures found are conventional implicatures and non-conventional implicatures. In the use of presuppositions, structural, lexical, nonfactive and factual presuppositions were found.